Analisis Realisasi Pendapatan Daerah pada Kabupaten dan Kota di Provinsi Sumatera Utara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to: 1) identify and analyze the degree of fiscal decentralization and the level of financial independence of regencies and cities in North Sumatra Province during the period 2015–2024; and 2) analyze the variation in regional revenue realization based on its components, as well as the variation in regional financial capacity across regencies/cities during the same period. The methods used in this research include the Fiscal Decentralization Degree Ratio (DDF), the Regional Financial Independence Ratio (RKKD), and a Two-Way ANOVA test, supported by SPSS 20 software. The findings show that the degree of fiscal decentralization remains relatively low from year to year, indicating a strong dependence on central government transfers. Similarly, the regional financial independence ratio is also categorized as low, with an instructive pattern of relationship, meaning that regional governments still have limited ability to finance development needs independently. The Two-Way ANOVA test results reveal significant differences in regional revenue realization both across regencies/cities and across years within the study period. The largest variations are attributed to the differing characteristics of each regency/city, including economic potential, effectiveness in managing locally generated revenue, and variations in regional fiscal structures. These findings highlight the importance of enhancing fiscal capacity and optimizing local revenue sources throughout North Sumatra.